PELAKSANAAN PROGRAM PELATIHAN TALENT CLASS DI PKBM KAK SETO BEKASI - Syahrial, Syahrial Azhar Dananta; Santika, Tika; Suminar, Uum (IKIP Siliwangi, 2025)
It aims to describe the implementation of the Talent Class training program at PKBM Kak Seto Bekasi and to describe the supporting and inhibiting factors of the Talent Class training program at PKBM Kak Seto Bekasi. This research applies a qualitative approach with the research method used for this research is the case study method. Data collection techniques by means of observation, interviews and documentation. The results of this study PKBM Kak Seto Bekasi creates space for students to explore and develop their own potential talents and interests, To be able to support these goals, it is necessary to implement a talent class training program that can help students to find and develop their potential until they become proficient. The supporting factors of this program include the quality of human resources (HR) of the teachers, as well as the availability and quality of adequate facilities and infrastructure. Competent and experienced teachers are instrumental in creating an inspiring and effective learning environment, where they are not only able to deliver the material well, but also motivate and guide students to reach their maximum potential. In addition, the existence of complete and quality facilities and infrastructure, such as comfortable classrooms, sophisticated learning equipment, and other supporting facilities, is essential in supporting an optimal teaching and learning process. Thus, the combination of qualified teachers and adequate facilities will significantly support the success of the Talent Class program. The main inhibiting factor in the implementation of Talent Class Dancing and Cooking is participant involvement, as there are still many individuals who have not been able to participate directly in these activities. This can be due to various reasons, such as time constraints, location, accessibility, or even a lack of information regarding the schedule and benefits of the Talent Class itself. As a result, the potential of the Talent Class cannot be fully maximized, considering that active participation from all prospective participants is very important to achieve the expected talent development goals.